Accessibility to, and Equal Opportunity for Education for Poverty Reduction in Nigeria : The National Economic Empowerment and Development Strategy (NEEDS) Perspective - Sani , Haruna; Soon, Jan-Jan; Cheah, Yong Kang (Society & Sustainability, 2019)
Prior literature has revealed that access to education and equal opportunity for education, are some of the major steps taken by the National Economic Empowerment and Development Strategy (NEEDS) program to tackle the problem of poverty through the education sector in Nigeria. However, most studies on NEEDS and education have failed to address the effects of education under the program on poverty reduction. As NEEDS is primarily set to achieve poverty reduction in Nigeria, this study, therefore, examines the relationship between the accessibility and equal opportunity for education under the NEEDS and perceived poverty reduction through investigating the educational impacts of NEEDS on poverty reduction. The paper suggests that for educational policies to serve in reducing poverty, such policies must be implemented in the context of poverty reduction; must involve seasoned teachers and administrators; and must conduct teacher-capability verification to flush out and retrain unqualified teachers. Given adequate infrastructure and funding, and if well adopted, the measures, if employed would bring about self-reliance, self-employment, income generation, and poverty reduction.